Escherichia coli expressed flagellin C (FliC) of Salmonella Typhi improved the protective efficacy of YopE against plague infection. Issue 1 (3rd January 2019) - Verma, Shailendra K.; Gupta, Ankit; Batra, Lalit; Tuteja, Urmil
Abstract: In the current antibiotic resistance scenario, vaccines may provide best defense against lethal bacterial diseases. So far, there is no ideal vaccine available against plague. Despite providing complete protection in small animal models, F1/LcrV based vaccine failed to provide ideal protection in non human primates. Here, we cloned, expressed and purified YopE of Yersinia pestis and flagellin C (FliC) of Salmonella Typhi. However the best possible protection needs the significant induction of IFN-γ and TNF-α. To determine the protective potential of the recombinant YopE alone or in formulation with FliC, Balb/C mice were immunized subcutaneously. The formulations were prepared with alum, a human compatible adjuvant. In our studies, the combination of YopE + FliC induced significantly strong humoral and cellular immune responses. A combination of YopE + FliC provided 83% protection whereas YopE alone provided only 50% against 100LD50 of Y. pestis in a mouse model.